The Syriac Legal Documents of the 3rd Century CE (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2025., 2025)
This book provides a re-edition and translation of the Syriac legal parchments of the mid 3rd century CE from Upper Mesopotamia, along with extensive commentary. These documents constitute our earliest significant evidence of the Syriac language and script, since only short epigraphs on stone and in mosaics survive otherwise. The texts are reproduced in Syriac script and in transliteration, while plates of the documents and script charts are also included, along with chapters devoted to script and language (in the context of the development of the later Classical Syriac forms) and to law (in the context of the adaptation of Aramaic law to Romanization).